2013
DOI: 10.1080/02643294.2013.803958
|View full text |Cite
|
Sign up to set email alerts
|

Short-term memory, working memory, and syntactic comprehension in aphasia

Abstract: Sixty one people with aphasia were tested on ten tests of short term memory (STM) and for the ability to use syntactic structure to determine the meanings of eleven types of sentences in three tasks – object manipulation, picture matching and picture matching with self-paced listening. Multilevel models showed relationships between measures of the ability to retain and manipulate item and order information in STM and accuracy and RT, and a greater relationship between these STM measures and accuracy and RT for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
72
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(87 citation statements)
references
References 114 publications
(143 reference statements)
7
72
1
Order By: Relevance
“…Working memory is not just about storage capacity, indeed, research with healthy adult readers suggests that for text comprehension, the important factor is the ability to allocate attention and control relevant information at any one moment (McVay & Kane, 2012). Impairments in working memory may therefore interact with linguistic deficits (Caplan, Michaud, & Hufford, 2013). For example, difficulty in retrieving relevant information via lexical or syntactic processes will be further compounded by difficulties in deploying that information to build a rich representation of the text (i.e., the situation model).…”
Section: Introductionmentioning
confidence: 98%
“…Working memory is not just about storage capacity, indeed, research with healthy adult readers suggests that for text comprehension, the important factor is the ability to allocate attention and control relevant information at any one moment (McVay & Kane, 2012). Impairments in working memory may therefore interact with linguistic deficits (Caplan, Michaud, & Hufford, 2013). For example, difficulty in retrieving relevant information via lexical or syntactic processes will be further compounded by difficulties in deploying that information to build a rich representation of the text (i.e., the situation model).…”
Section: Introductionmentioning
confidence: 98%
“…In aphasia, the processing of sentences is considered to be heavily dependent on other cognitive functions such as verbal working memory (Caplan et al, 2013) and associated with left IFG (Binder et al, 2009;Binder et al, 2005). In contrast, activity in the left AG associated with semantic processing has been widely reported (Price, 2010) and indeed, a meta-analysis on semantics by Binder et al (2009) identified this region as being the most routinely activated in response to semantic-based tasks.…”
Section: Discussionmentioning
confidence: 99%
“…Sentence level processing is considered to rely heavily on other cognitive functions, in particular verbal working memory (Caplan, Michaud, & Hufford, 2013). Therefore, the task-related prefrontal activity may actually reflect an increased requirement for attention and cognitive control mechanisms (Geranmayeh, Brownsett, & Wise, 2014) which are reduced in the acute phase, increased in the subacute phase and then return to normal activation patterns in the left hemisphere language areas in the chronic phase once support from the right hemisphere is no longer required (Saur et al, 2006) (this is covered in more depth in the discussion in Chapter 5).…”
Section: Stages Of Recoverymentioning
confidence: 99%
See 2 more Smart Citations